Study On Earnings Management To Exceed Psychological Thresholds By Malaysian Public Listed Companies - Mohamad, Musthafa (2009)
Earnings represent the single most important item in the financial reports. Earnings are closely monitored by several parties including financial analysts, executives, and boards of directors etc. The significance of earnings is further emphasized by the fact that the long-term stock returns are overwhelming explained by the firm\'s cumulative earnings. Earnings also have implications for senior executives\' employment and compensation benefits. Hence, executives possess strong incentives to manage earnings by exploiting the accounting flexibility permitted under the Generally Accepted Accounting Principles (GAAP).